2011
DOI: 10.1177/1078345810385916
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Opt-Out Programs at Los Angeles County Jail: A Gateway to Novel Research and Interventions

Abstract: Routine opt-out screening and vaccination programs are effective methods for improving public health in correctional populations. Jail-based rapid testing for HIV, hepatitis B and C, tuberculosis, syphilis, gonorrhea, and chlamydia can improve urban health by increasing diagnosis and linkage to care for infectious diseases. In addition, jail-based vaccination programs would significantly benefit community health and lower costs associated with tertiary level care. The paucity of ethical and rigorous scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…There is evidence to suggest that median length of stay for jail inmates can be as low as 2 days. 1,22 This was also demonstrated by our data, which showed that fewer than half the women with chlamydia or gonorrhea were treated in custody with the primary reason for lack of treatment relating to release from custody before laboratory results became available (range: 3-7 days after testing). In the event that an inmate with chlamydia or gonorrhea was released untreated, a health department community worker would follow up and provide field-delivered therapy, partner elicitation and notification, and health education and counseling, as appropriate.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There is evidence to suggest that median length of stay for jail inmates can be as low as 2 days. 1,22 This was also demonstrated by our data, which showed that fewer than half the women with chlamydia or gonorrhea were treated in custody with the primary reason for lack of treatment relating to release from custody before laboratory results became available (range: 3-7 days after testing). In the event that an inmate with chlamydia or gonorrhea was released untreated, a health department community worker would follow up and provide field-delivered therapy, partner elicitation and notification, and health education and counseling, as appropriate.…”
Section: Discussionsupporting
confidence: 68%
“…21 Women, who are housed in a separate facility from men, comprise a minority of the inmate population, with roughly 27 000 bookings per year, 22 and an average daily census of 2000 inmates. Each week, approximately 500 women are processed through the women’s inmate reception center where they undergo booking procedures including medical screening (oral communication, M. Malek, LASD, June 2013).…”
Section: Methodsmentioning
confidence: 99%
“…LACJ’s average daily incarcerated population is approximately 19,000 (87% male), and 1.6–2.0% of its male population at any given time is known to have HIV (Personal communication; Cox G, LASD Medical Service Bureau). At the time of this study, the mean and median lengths of stay for men in the LASD jails were respectively 42 and 15 days (Malek, et al, 2011), and 68% of LASD’s arrests of known HIV-positive males were for substance misuse offenses, including alcohol-related offenses (Internal report LASD Medical Service Bureau, 2010; Cox, Malek, & Deadmond). Approximately half of the male and male-to-female transgender HIV-positive incarcerated persons interviewed for this study resided in a protected custody unit designed for self-identified gay men and male-to-female transgender women.…”
Section: Methodsmentioning
confidence: 99%
“…Rapid HIV testing in jails may be used to expedite notification of results to both patient and provider and thus facilitate a more expedited evaluation for ART as well as expedite partner notification and risk reduction. 9,[14][15][16] Evaluation and treatment algorithms that can be implemented following a new HIV diagnosis, or upon knowledge that someone with chronic HIV infection has been incarcerated, must be developed. The removal of structural barriers to the delivery of HIV care will enable more efficient evaluation and consideration for ART initiation prior to jail release.…”
Section: Discussionmentioning
confidence: 99%